PLA / PPC degradable spinning material and preparation method thereof

By combining modified composite montmorillonite and rice straw fibers, PLA/PPC degradable spinning materials with high mechanical properties and biocompatibility were prepared, which solved the problem of poor tensile strength of existing materials and expanded its application field.

CN120383815APending Publication Date: 2025-07-29YUANJIA BIOTECHNOLOGY (GUANGDONG) CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510605385.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-12
Publication Date
2025-07-29

AI Technical Summary

Technical Problem

The poor tensile strength of existing PLA/PPC biodegradable composites limits its application.

Method used

The PLA/PPC degradable spinning materials are prepared by melt blending and extrusion by melt blending and extrusion, and modified composite montmorillonite, rice straw fiber, rice straw fiber, crosslinking agent, antioxidant, maleic anhydride grafting PLA compatible agent and catalyst. The modified composite montmorillonite, rice straw fiber and other components are used to improve the mechanical properties and biocompatibility of the materials.

Benefits of technology

It significantly improves the mechanical properties and biocompatibility of PLA/PPC degradable spinning materials, enhances the strength and toughness of the materials, and expands its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005398060180000091
    Figure BDA0005398060180000091
  • Figure BDA0005398060180000101
    Figure BDA0005398060180000101
Patent Text Reader

Abstract

The invention belongs to the technical field of biodegradable high polymer materials, and particularly discloses a PLA / PPC degradable spinning material and a preparation method thereof. The PLA / PPC degradable spinning material is prepared from the following raw materials in parts by weight: 65 to 75 parts of terminated polypropylene carbonate, 15 to 20 parts of polylactic acid, 1 to 2 parts of epoxidized soybean oil, 7 to 10 parts of composite Na-montmorillonite, 3 to 5 parts of light calcium carbonate, 6 to 9 parts of rice straw fiber, 0.6 to 0.8 part of cross-linking agent, 0.2 to 0.5 part of antioxidant, 1 to 2 parts of maleic anhydride grafted PLA compatilizer, 0.07 to 0.01 part of catalyst and 0.3 to 0.5 part of silicone. Various raw materials are mixed, so that the mechanical property of the material is remarkably improved, the material has good strength and toughness, and the comprehensive performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of biodegradable polymer materials, and in particular to a PLA / PPC degradable spinning material and a preparation method thereof. Background Art

[0002] PLA / PPC biodegradable spinning material is a high-performance biodegradable composite material. Its raw materials typically include PLA, PPC, a crosslinker, an antioxidant, a catalyst, and a lubricant. Through melt blending, a uniform composite material is formed. The melted composite material is then spun into fibers or films. It is widely used in textiles, packaging, agriculture, and biomedicine.

[0003] The prior art discloses a PPC / PLA composite material and a preparation method thereof. Specifically, blocked polypropylene carbonate, polylactic acid, a crosslinking agent, an antioxidant, a catalyst, and a lubricant are uniformly mixed to obtain a mixture, and the mixture is added to a twin-screw extruder, melt-blended, drawn into strands, and pelletized to obtain the PPC / PLA composite material.

[0004] The prepared PPC / PLA composite material has good optical properties and is completely biodegradable, which improves the toughness of the PPC / PLA composite material. However, there is still a problem of poor tensile strength, which limits the application of the composite material. Summary of the Invention

[0005] In order to improve the problem of poor tensile strength of PLA / PPC biodegradable composite materials, the present application provides a PLA / PPC degradable spinning material and a preparation method thereof.

[0006] This application provides a PLA / PPC biodegradable spinning material, which adopts the following technical solution: A PLA / PPC biodegradable spinning material comprises the following raw materials, measured in parts by weight: 65-75 parts of end-capped polypropylene carbonate, 15-20 parts of polylactic acid, 1-2 parts of epoxidized soybean oil, 7-10 parts of composite Na-montmorillonite, 3-5 parts of light calcium carbonate, 6-9 parts of rice straw fiber, 0.6-0.8 parts of a crosslinking agent, 0.2-0.5 parts of an antioxidant, 1-2 parts of a maleic anhydride-grafted PLA compatibilizer, 0.07-0.01 parts of a catalyst, and 0.3-0.5 parts of silicone.

[0007] By adopting the above technical solutions, the capped poly(propylene carbonate) has good flexibility, biocompatibility and thermal stability, and polylactic acid has good biocompatibility and mechanical strength. When combined with the capped poly(propylene carbonate), the rigidity and heat resistance of the material are improved. In the maleic anhydride grafted PLA compatibilizer, the maleic anhydride group reacts with the terminal hydroxyl group of PPC to form an ester bond, and at the same time, the PLA segment is entangled with the matrix PLA molecular chain to achieve "chemical - physical" double compatibilization. Epoxidized soybean oil, as a bio - based plasticizer, improves the flexibility and processing performance of the material while maintaining the biodegradability of the material.

[0008] The modified composite montmorillonite has good mechanical properties (such as tensile strength), barrier properties and thermal stability, which improve the mechanical properties of the material. The pores of the light calcium carbonate filling system improve the rigidity and dimensional stability of the material. Rice straw fiber has good biocompatibility and degradability, and when combined with the modified composite montmorillonite, it further improves the mechanical properties of the material.

[0009] The cross - linker improves the mechanical properties and heat resistance of the material. By forming a cross - linked network structure, the strength of the material is enhanced. The antioxidant prevents the material from undergoing oxidative degradation during processing and use, and extends the service life of the material. The catalyst is used to accelerate the polymerization reaction or cross - linking reaction, improve the production efficiency, and silicone improves the surface properties of the material, reduces the surface tension and improves the processing performance of the material.

[0010] The composite material formed by the capped poly(propylene carbonate) and polylactic acid can be naturally degraded after use, reducing environmental pollution. The addition of modified montmorillonite, light calcium carbonate and rice straw fiber significantly improves the mechanical properties of the material, which has good strength and toughness. The addition of epoxidized soybean oil and silicone improves the flexibility and processing performance of the material, and the use of maleic anhydride grafted PLA compatibilizer improves the compatibility between PLA and PPC, further improving the comprehensive performance of the material.

[0011] Preferably, the preparation method of the composite Na - montmorillonite includes the following steps: (1) Dispersing Na - montmorillonite in deionized water, adding cetyltrimethylammonium bromide, stirring at 60 - 65 °C for 1.5 - 2 h, filtering, drying and pulverizing to obtain organically modified montmorillonite; (2) Dispersing modified cellulose nanocrystals in deionized water, adding the organically modified montmorillonite obtained in step (1) and sodium polyacrylate, stirring at 70 - 75 °C for 1 - 2 h, filtering to obtain a mixture, spraying lignin solution on the surface of the mixture, stirring evenly and drying to obtain the composite Na - montmorillonite.

[0012] By adopting the above technical solutions, Na-montmorillonite has good adsorption and ion exchange capabilities. The long-chain alkyl part of cetyltrimethylammonium bromide can be inserted into the interlayer of montmorillonite, increasing the interlayer spacing, making the montmorillonite have better flexibility and compatibility with the organic phase, and better loading with other components subsequently.

[0013] The modified cellulose nanocrystals have good mechanical properties and biocompatibility. The interlayer spacing of the organically modified montmorillonite increases, and the modified cellulose nanocrystals are better loaded in the structure of the organically modified montmorillonite, improving the mechanical properties such as the strength and modulus of the system. Sodium polyacrylate has good dispersibility, which helps the modified cellulose nanocrystals and the organically modified montmorillonite to be evenly dispersed in water, contributing to the uniform loading of the modified cellulose nanocrystals in the structure of the organically modified montmorillonite and improving the mechanical properties of the mixture.

[0014] By spraying lignin solution on the surface of the mixture, the lignin solution forms a film to coat the modified cellulose nanocrystals and the organically modified montmorillonite, making the modified cellulose nanocrystals and the organically modified montmorillonite adhere tightly, increasing the mechanical properties of the modified composite montmorillonite. The synergistic effect of Na-montmorillonite, modified cellulose nanocrystals and lignin improves the mechanical properties of the PLA / PPC composite material, making it have higher tensile strength, modulus and stability.

[0015] Preferably, the mass ratio of the Na-montmorillonite, modified cellulose nanocrystals and lignin solution is 1:0.6 - 0.7:0.2 - 0.3.

[0016] By adopting the above technical solutions, further limiting the mass ratio of the Na-montmorillonite, modified cellulose nanocrystals and lignin solution within a certain range improves the comprehensive performance of the modified composite montmorillonite. The hydroxyl groups on the surface of the modified cellulose nanocrystals form hydrogen bonds with the polar groups on the surface of the organically modified montmorillonite, making the modified cellulose nanocrystals loaded in the Na-montmorillonite structure. The lignin solution has good film-forming property and viscosity, making the modified cellulose nanocrystals adhere tightly to the Na-montmorillonite, increasing the structural strength of the modified composite montmorillonite. Subsequently, when applied to the PLA / PPC degradable spinning material, the mechanical properties of the material are improved. The mixing of the Na-montmorillonite, modified cellulose nanocrystals and lignin solution significantly improves the mechanical properties, thermal stability, processing performance, biocompatibility and degradability of the material through synergistic effects.

[0017] Preferably, the preparation method of the modified cellulose nanocrystals includes the following steps: dispersing cellulose nanocrystals in acetic acid solution, adding silane coupling agent KH-550, ultrasonicating for 1 - 2 h, washing and drying to obtain treated cellulose nanocrystals; dispersing the treated cellulose nanocrystals in deionized water, adding nano-silica and sodium alginate, stirring at 75 - 80 °C for 2 - 3 h, and drying to obtain modified cellulose nanocrystals.

[0018] By adopting the above technical solution, the acetic acid solution helps the uniform dispersion of cellulose nanocrystals. The silane coupling agent KH-550 can chemically react with the hydroxyl groups on the surface of cellulose nanocrystals to introduce amino functional groups, improve the surface activity of cellulose nanocrystals, and also enhance the compatibility between subsequent cellulose nanocrystals and silica. The treated cellulose nanocrystals are dispersed in deionized water, and nano-silica and sodium alginate are added. Nano-silica has a high specific surface area and good mechanical properties. Nano-silica is loaded on the surface of cellulose nanocrystals to enhance the mechanical properties of cellulose nanocrystals. It has good film-forming properties and biocompatibility, enabling nano-silica to adhere tightly to cellulose nanocrystals, and the obtained modified cellulose nanocrystals have good mechanical properties, and subsequently improve the mechanical properties of the modified composite montmorillonite.

[0019] Preferably, the rice straw fibers are pretreated. The pretreatment method of the rice straw fibers includes the following steps: (1) Coarsely cut the rice straw fibers, then disperse them in absolute ethanol, filter, crush, sieve, and then disperse them in an aqueous sodium sulfite solution, stir at a temperature of 70-75 °C for 2-3 h, and dry to obtain surface-modified straw fibers; (2) Disperse the modified collagen fibers in deionized water, add the surface-modified straw fibers, hydrochloric acid, chitosan, and hyaluronic acid obtained in step (1), stir at a temperature of 70-75 °C for 1-2 h, and dry to obtain pretreated rice straw fibers.

[0020] By adopting the above technical solution, absolute ethanol removes the impurities and waxes on the surface of rice straw fibers, and sodium sulfite removes the lignin and hemicellulose on the surface of straw fibers, while introducing polar groups to improve the surface activity of straw fibers.

[0021] The modified collagen fibers have better mechanical properties and biocompatibility. By adding surface-modified straw fibers, hydrochloric acid, chitosan, and hyaluronic acid, the modified collagen fibers are better adsorbed on the surface and pores of the surface-modified straw fibers, improving the mechanical properties of the modified straw fibers. Hydrochloric acid improves the surface activity of the modified collagen fibers and the surface-modified straw fibers, enabling the better composite of the modified collagen fibers and the surface-modified straw fibers. Chitosan has good biocompatibility and adhesiveness, and forms hydrogen bonds with the polar groups on the surfaces of the modified collagen fibers and the surface-modified straw fibers respectively, enhancing the binding force between the fibers.

[0022] Hyaluronic acid has good moisturizing properties and biocompatibility, further enhancing the binding force between the modified collagen fibers and the surface-modified straw fibers, and at the same time improving the flexibility of the composite material. Subsequently, it is applied to PLA / PPC degradable spinning materials to improve the mechanical properties and flexibility of the materials, and contribute to the extended use of the materials.

[0023] Preferably, the mass ratio of the rice straw fiber, the modified collagen fiber, and the chitosan is 1:0.5 - 0.6:0.1 - 0.2.

[0024] By adopting the above technical solution, the mass ratio of the rice straw fiber, the modified collagen fiber, and the chitosan is further limited within a certain range, and the pretreated rice straw fiber obtained has excellent comprehensive properties. The rice straw fiber has high strength, modulus, thermal stability, and biocompatibility. The modified collagen fiber has excellent biocompatibility, toughness, and impact resistance. The modified collagen fiber can be loaded on the surface and pores of the rice straw fiber to improve the mechanical properties and flexibility of the rice straw fiber. Chitosan has good biocompatibility, biodegradability, and adhesiveness, making the rice straw fiber and the modified collagen fiber adhere tightly, increasing the performance stability of the rice straw fiber, and subsequently improving the mechanical strength and flexibility of the PLA / PPC degradable spinning material.

[0025] The mixed use of the rice straw fiber, the modified collagen fiber, and the chitosan improves the mechanical properties, thermal stability, biocompatibility, and antibacterial properties of the PLA / PPC composite material. This composite material not only has good mechanical properties and thermal stability but also has multifunctional properties such as antibacterial and biocompatible properties, making it have broad application prospects in multiple fields.

[0026] Preferably, the preparation method of the modified collagen fiber includes the following steps: Dispersing the collagen fiber in an aqueous citric acid solution, adding vegetable tannin, stirring for 1 - 2 h, washing and drying, then dispersing it in deionized water, adding graphene, starch, and polyethylene glycol, stirring for 2 - 3 h, and drying to obtain the modified collagen fiber.

[0027] By adopting the above technical solution, citric acid adjusts the pH value of the solution to better disperse the collagen fiber in an acidic environment, increasing the surface activity of the fiber. Vegetable tannin has good antioxidant and antibacterial properties and forms hydrogen bonds or covalent bonds with the amino groups in the collagen fiber, further enhancing the surface activity and stability of the fiber.

[0028] Adding graphene, starch, and polyethylene glycol, graphene has a high specific surface area and excellent mechanical properties and can adsorb on the surface of the collagen fiber to increase the strength and toughness of the collagen fiber. Starch has good film-forming properties and biocompatibility, not only making graphene and collagen fiber evenly dispersed in water but also making graphene stably loaded on the surface of the collagen fiber. Polyethylene glycol has good lubricity and dispersibility, improving the flexibility of the fiber. The mixed use of graphene, starch, PEG, and collagen fiber improves the mechanical properties, thermal stability, biocompatibility, and processing properties of the PLA / PPC composite material.

[0029] Preferably, the crosslinking agent is one or more of furan dialdehyde, indole-3,6-dialdehyde, vanillin, cumin aldehyde, lauric aldehyde, 5-hydroxymethylfurfural.

[0030] By adopting the above technical solution, the crosslinking agent forms a crosslinked network, significantly improving the tensile strength and modulus of the PLA / PPC composite material, enhancing the stability of the material in a high-temperature environment, improving the processing performance of the PLA / PPC composite material, and making it more suitable for the spinning process.

[0031] Preferably, the antioxidant is one or more of antioxidant 1010, antioxidant 1035, antioxidant 1098, antioxidant 1135, antioxidant 3114, antioxidant 1024.

[0032] By adopting the above technical solution, the antioxidant has good thermal stability, provides long-term antioxidant protection, and improves the performance and service life of the PLA / PPC degradable spinning material.

[0033] In a second aspect, the present application also provides a preparation method of a PLA / PPC degradable spinning material, including the following steps: uniformly mixing the end-capped poly(propylene carbonate), polylactic acid, epoxidized soybean oil, modified composite montmorillonite, light calcium carbonate, rice straw fiber, crosslinking agent, antioxidant, catalyst, and silicone, and performing melt blending and extrusion to obtain the PLA / PPC degradable spinning material.

[0034] By adopting the above technical solution, with the above preparation method, the process time is short, the operation is simple, the production efficiency of preparing the PLA / PPC degradable spinning material is improved, and the obtained PLA / PPC degradable spinning material has good mechanical properties.

[0035] In summary, the present application has the following beneficial effects: 1. The modified composite montmorillonite in the present application has good mechanical properties (such as tensile strength), barrier properties, and thermal stability, improving the mechanical properties of the material, and the light calcium carbonate fills the pores of the system, improving the rigidity and dimensional stability of the material.

[0036] 2. In the present application, multiple components are combined, and modified montmorillonite, light calcium carbonate, and rice straw fiber are added, significantly improving the mechanical properties of the material, having good strength and toughness, and further improving the comprehensive performance of the material.

[0037] 3. The rice straw fiber in the present application has good biocompatibility and degradability, and in combination with the modified composite montmorillonite, further improves the mechanical properties of the material. Detailed Embodiments

[0038] The following further elaborates on the present application with reference to examples.

[0039] The raw materials used in the examples and comparative examples are all commercially available.

[0040] Preparation Examples of Composite Na-Montmorillonite Preparation Example 1 The preparation method of the composite Na-montmorillonite includes the following steps: (1) Disperse 10 kg of Na-montmorillonite in 50 L of deionized water, add 0.5 kg of cetyltrimethylammonium bromide, stir at 63 °C for 2 h, filter, dry, and pulverize to obtain organically modified montmorillonite; (2) Disperse the modified cellulose nanocrystals in 100 L of deionized water, add the organically modified montmorillonite obtained in step (1) and 2 kg of sodium polyacrylate, stir at 73 °C for 1.5 h, filter to obtain a mixture, spray a lignin solution on the surface of the mixture, stir evenly, and dry to obtain the composite Na-montmorillonite.

[0041] The Na-montmorillonite was purchased from Chenyuan Mineral Products Processing Factory in Lingshou County. Lignin solution: Disperse 5 kg of lignin in 20 L of deionized water, add 1 kg of xanthan gum, stir evenly to obtain the lignin solution, and take the required amount to prepare the composite Na-montmorillonite.

[0042] The mass ratio of Na-montmorillonite, modified cellulose nanocrystals, and lignin solution is 1:0.6:0.2.

[0043] The preparation method of the modified cellulose nanocrystals includes the following steps: Disperse 9 kg of cellulose nanocrystals in 25 L of acetic acid solution with a mass fraction of 5%, add 1 kg of silane coupling agent KH-550, ultrasonicate for 1.6 h, wash and dry to obtain the treated cellulose nanocrystals. Disperse the treated cellulose nanocrystals in 50 L of deionized water, add 3 kg of nano-silica and 1 kg of sodium alginate, stir at 78 °C for 2.6 h, and dry to obtain the modified cellulose nanocrystals.

[0044] Preparation Example 2 The difference from Preparation Example 1 is that in step (2), the modified montmorillonite is not added.

[0045] Preparation Example 3 The difference from Preparation Example 1 is that in step (2), the lignin solution is not added.

[0046] Preparation Example 4 The difference from Preparation Example 1 is that the mass ratio of Na-montmorillonite, modified cellulose nanocrystals, and lignin solution is 1:0.7:0.3.

[0047] Preparation Example 5 The difference from Preparation Example 1 lies in that the mass ratio of Na-montmorillonite, modified cellulose nanocrystals and lignin solution is 1:0.1:0.6.

[0048] Preparation Example 6 The difference from Preparation Example 1 lies in that in the preparation method of the modified cellulose nanocrystals, nano-silica is not added.

[0049] Preparation Example 7 The difference from Preparation Example 1 lies in that in the preparation method of the modified cellulose nanocrystals, sodium alginate is not added.

[0050] Preparation Example of Pretreatment of Rice Straw Fibers Preparation Example 8 The rice straw fibers are pretreated. The pretreatment method of the rice straw fibers includes the following steps: (1) Coarsely cut 25 kg of rice straw fibers, then disperse them in 55 L of absolute ethanol, filter, crush, pass through a 10-mesh sieve, then disperse them in 50 L of an aqueous sodium sulfite solution with a mass fraction of 15%, stir at a temperature of 73 °C for 2.5 h, and dry to obtain surface-modified straw fibers; (2) Disperse the modified collagen fibers in 60 L of deionized water, add the surface-modified straw fibers obtained in step (1), 1 L of hydrochloric acid, chitosan and 2 kg of hyaluronic acid, stir at a temperature of 73 °C for 1.5 h, and dry to obtain pretreated rice straw fibers.

[0051] The mass ratio of the rice straw fibers, the modified collagen fibers and chitosan is 1:0.5:0.2.

[0052] The preparation method of the modified collagen fibers includes the following steps: Disperse 15 kg of collagen fibers in 30 L of an aqueous citric acid solution with a mass fraction of 8%, add 2 kg of plant tannins, stir for 1.6 h, wash and dry, then disperse them in 60 L of deionized water, add 5 kg of graphene, 2 kg of corn starch, 1 kg of polyethylene glycol, stir for 2.5 h, and dry to obtain modified collagen fibers.

[0053] The plant tannins are tea tannins, purchased from Ningbo Xifeng Biotechnology Co., Ltd.

[0054] Preparation Example 9 The difference from Preparation Example 8 lies in that in step (2), the modified collagen fibers are not added.

[0055] Preparation Example 10 The difference from Preparation Example 8 lies in that in step (2), chitosan is not added.

[0056] Preparation Example 11 The difference from Preparation Example 8 lies in that the mass ratio of the rice straw fibers, the modified collagen fibers and chitosan is 1:0.6:0.1.

[0057] Preparation Example 12 It is different from Preparation Example 8 in that the mass ratio of rice straw fiber, modified collagen fiber and chitosan is 1:0.08:0.45.

[0058] Preparation Example 13 It is different from Preparation Example 8 in that graphene is not added in the preparation method of the modified collagen fiber.

[0059] Preparation Example 14 It is different from Preparation Example 8 in that starch is not added in the preparation method of the modified collagen fiber. Examples

[0060] Example 1 A PLA / PPC degradable spinning material, by weight, comprises the following raw materials: 65 kg of end-capped poly(propylene carbonate), 15 kg of polylactic acid, 1 kg of epoxidized soybean oil, 10 kg of composite Na-montmorillonite, 3 kg of light calcium carbonate, 9 kg of rice straw fiber, 0.6 kg of crosslinking agent, 0.2 kg of antioxidant, 1 kg of maleic anhydride grafted PLA compatibilizer, 0.07 kg of catalyst, and 0.3 kg of silicone.

[0061] Preparation method of end-capped poly(propylene carbonate): Dry 90 kg of PPC for 3 h, mix it evenly with 3 kg of maleic anhydride, add it to a twin-screw extruder for end-capping treatment. The heating temperature of the twin-screw extruder is set at 160 °C, the rotation speed is 30 rpm, and the time is 6 min.

[0062] The catalyst is tetraphenylporphyrin iron, the crosslinking agent is furan dialdehyde, the antioxidant is antioxidant 1010, the maleic anhydride grafted PLA compatibilizer is purchased from Shanghai Wanluji Plastic Technology Co., Ltd., and the particles of light calcium carbonate are between 700 - 800 meshes.

[0063] The preparation method of the above PLA / PPC degradable spinning material comprises the following steps: Mix evenly the end-capped poly(propylene carbonate), polylactic acid, epoxidized soybean oil, modified composite montmorillonite, light calcium carbonate, rice straw fiber, crosslinking agent, antioxidant, catalyst, and silicone, and carry out melt blending and extrusion to obtain the PLA / PPC degradable spinning material.

[0064] The melt blending is carried out in a twin-screw extruder at a rotation speed of 60 r / min, and melt blending and extrusion are carried out at 160 °C.

[0065] The composite Na-montmorillonite is prepared by Preparation Example 1-1, and the rice straw fiber is commercially available and purchased from Zhuji Dudan Department Store.

[0066] Example 2 A PLA / PPC degradable spinning material, which is different from that of Example 1, includes the following raw materials by weight: 75 kg of end-capped poly(propylene carbonate), 20 kg of polylactic acid, 2 kg of epoxidized soybean oil, 7 kg of composite Na-montmorillonite, 5 kg of light calcium carbonate, 6 kg of rice straw fiber, 0.8 kg of cross-linking agent, 0.5 kg of antioxidant, 2 kg of maleic anhydride grafted PLA compatibilizer, 0.01 kg of catalyst, and 0.5 kg of silicone.

[0067] Example 3 A PLA / PPC degradable spinning material, which is different from that of Example 1, wherein the composite Na-montmorillonite is prepared by Preparation Example 2.

[0068] Example 4 A PLA / PPC degradable spinning material, which is different from that of Example 1, wherein the composite Na-montmorillonite is prepared by Preparation Example 3.

[0069] Example 5 A PLA / PPC degradable spinning material, which is different from that of Example 1, wherein the composite Na-montmorillonite is prepared by Preparation Example 4.

[0070] Example 6 A PLA / PPC degradable spinning material, which is different from that of Example 1, wherein the composite Na-montmorillonite is prepared by Preparation Example 5.

[0071] Example 7 A PLA / PPC degradable spinning material, which is different from that of Example 1, wherein the composite Na-montmorillonite is prepared by Preparation Example 6.

[0072] Example 8 A PLA / PPC degradable spinning material, which is different from that of Example 1, wherein the composite Na-montmorillonite is prepared by Preparation Example 7.

[0073] Example 9 A PLA / PPC degradable spinning material, which is different from that of Example 1, wherein the rice straw fiber is prepared by Preparation Example 8.

[0074] Example 10 A PLA / PPC degradable spinning material, which is different from that of Example 9, wherein the rice straw fiber is prepared by Preparation Example 9.

[0075] Example 11 A PLA / PPC degradable spinning material, which is different from that of Example 9, wherein the rice straw fiber is prepared by Preparation Example 10.

[0076] Example 12 A PLA / PPC degradable spinning material, which is different from Example 9 in that the rice straw fiber is prepared by Preparation Example 11.

[0077] Example 13 A PLA / PPC degradable spinning material, which is different from Example 9 in that the rice straw fiber is prepared by Preparation Example 12.

[0078] Example 14 A PLA / PPC degradable spinning material, which is different from Example 9 in that the rice straw fiber is prepared by Preparation Example 13.

[0079] Example 15 A PLA / PPC degradable spinning material, which is different from Example 9 in that the rice straw fiber is prepared by Preparation Example 14.

[0080] Comparative Example Comparative Example 1 A PLA / PPC degradable spinning material, which is different from Example 1 in that no composite Na-montmorillonite is added.

[0081] Comparative Example 2 A PLA / PPC degradable spinning material, which is different from Example 1 in that montmorillonite in equal amount is used to replace the composite Na-montmorillonite.

[0082] Comparative Example 3 A PLA / PPC degradable spinning material, which is different from Example 1 in that no rice straw fiber is added.

[0083] Performance Detection Test The PLA / PPC degradable spinning materials prepared in Examples 1 - 15 and Comparative Examples 1 - 3 were subjected to performance tests; Tested according to ISO527 standard, with a speed of 8 mm / min, the tensile strength and tensile elastic modulus of the PLA / PPC degradable spinning material were tested; Tested according to ASTM D638 standard, with a speed of 8 mm / min, the elongation at break of the PLA / PPC degradable spinning material was tested; tested according to ASTM D256 standard, with a pendulum mass of 0.671 kg, a speed of 0.42 m / s, and a pendulum energy of 4.5 J, the notched impact strength of the PLA / PPC degradable spinning material was tested, and the test results are shown in Table 1.

[0084] Table 1 Test Data of Examples and Comparative Examples As can be seen from Table 1, the PLA / PPC degradable spinning materials prepared in Examples 1-2 of this application have good mechanical properties and mechanical strength. Among them, the tensile strength of Example 1 is 68.5 MPa, the tensile elastic modulus is 2453 MPa, the elongation at break is 363.5%, and the notch impact strength is 84.2 KJ / m 2 . It can be seen that the materials prepared in this application have good strength and toughness. Each component cooperates with each other, improving the mechanical properties of the PLA / PPC degradable spinning materials and expanding the application of the materials.

[0085] In addition, the PLA / PPC degradable spinning material prepared in Example 1 was spun at a spinning temperature of 170 °C and a spinning speed of 800 m / min. The breaking strength of the obtained fiber was 3.8 cN / dtex, and the fiber diameter was 30 μm. The PLA / PPC degradable spinning material prepared in Example 2 was spun at a spinning temperature of 220 °C and a spinning speed of 1000 m / min. The breaking strength of the obtained fiber was 3.5 cN / dtex, and the fiber diameter was 28 μm. The PLA / PPC degradable spinning material prepared in Example 9 was spun at a spinning temperature of 200 °C and a spinning speed of 900 m / min. The breaking strength of the obtained fiber was 4.0 cN / dtex, and the fiber diameter was 29 μm. It can be seen that the PLA / PPC degradable spinning materials prepared in this application have good comprehensive properties, and the fibers obtained by spinning have excellent mechanical properties.

[0086] In the preparation methods of Examples 3-4 of the composite Na-montmorillonite, modified montmorillonite and lignin solution were not added respectively. In Examples 5-6, the mass ratios of Na-montmorillonite, modified cellulose nanocrystals and lignin solution were changed. As can be seen from Table 1, the test results of the tensile strength, tensile elastic modulus, elongation at break and notch impact strength of Examples 3-4 are significantly worse than those of Examples 1-2 and Example 5, while the test results of the corresponding properties of Example 6 are better than those of Examples 3-4, but worse than those of Examples 1-2 and Example 5. It shows that the lignin solution makes the modified cellulose nanocrystals adhere tightly to the Na-montmorillonite, increasing the structural strength of the modified composite montmorillonite. Subsequently, when applied to the PLA / PPC degradable spinning material, the mechanical properties of the material are improved. The mixing of Na-montmorillonite, modified cellulose nanocrystals and lignin solution significantly improves the mechanical properties, thermal stability and degradability of the material through synergistic effects.

[0087] In the preparation methods of modified cellulose nanocrystals in Examples 7 - 8, nano - silica and sodium alginate were not added respectively. It can be seen from Table 1 that the test results of the tensile strength, tensile elastic modulus, elongation at break, and notched impact strength of Examples 7 - 8 at 7 days were significantly worse than those of Examples 1 - 2, but better than those of Example 3. This indicates that nano - silica is loaded on the surface of cellulose nanocrystals, enhancing the mechanical properties of cellulose nanocrystals, and sodium alginate makes nano - silica adhere tightly to cellulose nanocrystals, resulting in modified cellulose nanocrystals with good mechanical properties, and subsequently improving the mechanical properties of modified composite montmorillonite.

[0088] In Example 9, the rice straw fiber was pretreated. It can be seen from Table 1 that the tensile strength of the material was 79.8 MPa, the tensile elastic modulus was 2473 MPa, the elongation at break was 382.3%, and the notched impact strength was 95.6 KJ / m 2 . It can be seen that pretreating the rice straw fiber significantly improved the comprehensive performance of the PLA / PPC biodegradable composite material, making the material have a wider range of applications.

[0089] In Example 10, modified collagen fiber was not added in the pretreatment method of rice straw fiber. In Example 11, chitosan was not added in the pretreatment method of rice straw fiber. In Examples 12 - 13, the mass ratios of rice straw fiber, modified collagen fiber, and chitosan were changed. It can be seen from Table 1 that the test results of the tensile strength, tensile elastic modulus, elongation at break, and notched impact strength of Examples 10 - 11 were significantly worse than those of Example 9 and Example 12, but better than those of Examples 1 - 2, while the test results of the corresponding properties of Example 13 were better than those of Examples 10 - 11, but worse than those of Example 9. This indicates that modified collagen fiber can be loaded on the surface and pores of rice straw fiber, improving the mechanical properties and flexibility of rice straw fiber, and chitosan makes rice straw fiber and modified collagen fiber adhere tightly, increasing the performance stability of rice straw fiber, and subsequently improving the mechanical strength and flexibility of the PLA / PPC degradable spinning material.

[0090] In the preparation methods of modified collagen fiber in Examples 14 - 15, graphene and starch were not added respectively. It can be seen from Table 1 that the test results of the tensile strength, tensile elastic modulus, elongation at break, and notched impact strength of Examples 14 - 15 were significantly worse than those of Example 9, but better than those of Example 10. This indicates that graphene can adsorb on the surface of collagen fiber, increasing the strength and toughness of collagen fiber, and starch makes graphene stably loaded on the surface of collagen fiber, improving the mechanical properties of the PLA / PPC composite material.

[0091] In Comparative Example 1 and Comparative Example 3, the composite Na-montmorillonite and rice straw fiber were not added respectively. As can be seen from Table 1, the test results of the tensile strength, tensile elastic modulus, elongation at break, and notched impact strength of Comparative Example 1 and Comparative Example 3 were significantly worse than those of Examples 1-2, indicating that the modified composite montmorillonite has good mechanical properties (such as tensile strength), barrier properties, and thermal stability, improving the mechanical properties of the material; the rice straw fiber has good biocompatibility, mechanical properties, and degradability, and when combined with the modified composite montmorillonite, it further improves the mechanical properties of the material.

[0092] In Comparative Example 2, an equal amount of montmorillonite was used to replace the composite Na-montmorillonite. As can be seen from Table 1, the test results of the tensile strength, tensile elastic modulus, elongation at break, and notched impact strength of Comparative Example 2 were significantly worse than those of Examples 1-2, but better than those of Comparative Example 1 and Comparative Example 3, indicating that the modified montmorillonite of the present application has excellent mechanical properties and can improve the comprehensive properties of the PLA / PPC composite material when applied.

[0093] This specific embodiment is only an explanation of the present application and does not limit the present application. Those skilled in the art can make modifications without creative contributions to this embodiment according to needs after reading this specification, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A PLA / PPC degradable spinning material, characterized in that, By weight parts, it includes the following raw materials: 65 - 75 parts of end - capped poly(propylene carbonate), 15 - 20 parts of polylactic acid, 1 - 2 parts of epoxidized soybean oil, 7 - 10 parts of composite Na - montmorillonite, 3 - 5 parts of light calcium carbonate, 6 - 9 parts of rice straw fiber, 0.6 - 0.8 parts of cross - linker, 0.2 - 0.5 parts of antioxidant, 1 - 2 parts of maleic anhydride - grafted PLA compatibilizer, 0.07 - 0.01 parts of catalyst, 0.3 - 0.5 parts of silicone.

2. The PLA / PPC degradable spinning material according to claim 1, wherein The preparation method of the composite Na - montmorillonite includes the following steps: (1) Disperse Na - montmorillonite in deionized water, add cetyltrimethylammonium bromide, stir at 60 - 65 °C for 1.5 - 2 h, filter, dry, and pulverize to obtain organically modified montmorillonite; (2) Disperse modified cellulose nanocrystals in deionized water, add the organically modified montmorillonite obtained in step (1) and sodium polyacrylate, stir at 70 - 75 °C for 1 - 2 h, filter to obtain a mixture, spray lignin solution on the surface of the mixture, stir evenly, and dry to obtain composite Na - montmorillonite.

3. A PLA / PPC degradable spinning material according to claim 2, characterized in that, The mass ratio of the Na - montmorillonite, modified cellulose nanocrystals, and lignin solution is 1:0.6 - 0.7:0.2 - 0.

3.

4. A PLA / PPC degradable spinning material according to claim 2, characterized in that, The preparation method of the modified cellulose nanocrystals includes the following steps: Disperse cellulose nanocrystals in acetic acid solution, add silane coupling agent KH - 550, ultrasonic for 1 - 2 h, wash and dry to obtain treated cellulose nanocrystals. Disperse the treated cellulose nanocrystals in deionized water, add nano - silica and sodium alginate, stir at 75 - 80 °C for 2 - 3 h, and dry to obtain modified cellulose nanocrystals.

5. A PLA / PPC degradable spinning material according to claim 1, characterized in that Pre - treat the rice straw fiber. The pre - treatment method of the rice straw fiber includes the following steps: (1) Coarsely cut the rice straw fiber, then disperse it in absolute ethanol, filter, crush, screen, and then disperse it in an aqueous sodium sulfite solution, stir at 70 - 75 °C for 2 - 3 h, and dry to obtain surface - modified straw fiber; (2) Disperse the modified collagen fiber in deionized water, add the surface - modified straw fiber obtained in step (1), hydrochloric acid, chitosan, and hyaluronic acid, stir at 70 - 75 °C for 1 - 2 h, and dry to obtain pre - treated rice straw fiber.

6. The PLA / PPC degradable spinning material according to claim 5, characterized in that, The mass ratio of the rice straw fiber, modified collagen fiber, and chitosan is 1:0.5 - 0.6:0.1 - 0.

2.

7. A PLA / PPC degradable spinning material according to claim 5, characterized in that The preparation method of the modified collagen fiber includes the following steps: Disperse collagen fiber in citric acid aqueous solution, add plant tannins, stir for 1 - 2 h, wash and dry, and then disperse it in deionized water, add graphene, starch, and polyethylene glycol, stir for 2 - 3 h, and dry to obtain modified collagen fiber.

8. A PLA / PPC degradable spinning material according to claim 1, characterized in that, The cross - linker is one or more of furan - 2,5 - dialdehyde, indole - 3,6 - dialdehyde, vanillin, cumin aldehyde, lauraldehyde, 5 - hydroxymethylfurfural.

9. The PLA / PPC degradable spinning material according to claim 1, wherein, The antioxidant is one or more of antioxidant 1010, antioxidant 1035, antioxidant 1098, antioxidant 1135, antioxidant 3114, antioxidant 1024.

10. The preparation method of a PLA / PPC degradable spinning material according to claim 1, characterized in that, It includes the following steps: uniformly mixing the capped poly(propylene carbonate), polylactic acid, epoxidized soybean oil, modified composite montmorillonite, light calcium carbonate, rice straw fiber, crosslinking agent, antioxidant, catalyst, and silicone, followed by melt blending and extrusion to obtain the PLA / PPC degradable spinning material.

Citation Information

Cited By

  • PPC spun yarn and preparation method and application thereof

    CN121473032A

  • Fiber for anti-radiation fabric and preparation method thereof

    CN121593202A